The temperature dependent functionality of Brettanomyces bruxellensis strains in wort fermentations. Issue 3 (7th June 2019) - Tyrawa, Caroline; Preiss, Richard; Armstrong, Meagan; van der Merwe, George
Abstract : In recent years, Brettanomyces bruxellensis has found increasing application in brewery fermentations. Indeed, B. bruxellensis contributes to the flavour profile of many Belgian beers, typically during secondary or spontaneous fermentation. In North America, the yeast is used in primary fermentation to produce beers with ' Brett ' characteristics with 'fruity' and/or 'funky' sensory profiles associated with the production of volatile esters and phenols. However, little is understood about the factors that influence flavour metabolite production or fermentation rate in this yeast. Here, the impact of temperature is reported on fermentation efficiency, flavour metabolite production and carbon utilisation of one commonly used and eight poorly characterised B. bruxellensis strains during wort fermentation. A high degree of strain and temperature‐dependent variability was found in fermentation efficiency and metabolite production amongst B. bruxellensis strains. Further, fermentation efficiency and carbon utilisation were temperature dependent, while ester production increased at higher temperature and phenol production was strain and temperature independent. These results indicate significant strain and temperature dependent variation, suggesting the potential application of strain variability as a tool to achieve product diversity in B. bruxellensis primary fermentations. © 2019 The Institute of Brewing & Distilling